Barriers and Opportunities for Pollinator Gardening in Homeowners’ Associations - Laura A. Warner; Colby Silvert; John Diaz; Cody Gusto; Rachel Mallinger (EDIS, 2023)
Pollinator gardening has rapidly become recognized as an important component of conservation to combat the issues that have resulted from rapid urbanization. Residential yards can support pollinators and help to restore their habitats. Thus, an opportunity exists for Extension and other practitioners to encourage greater engagement in pollinator gardening. However, research has indicated unique perceived barriers exist among residents in homeowners’ associations (HOAs). By focusing on perceived barriers, Extension and other practitioners can encourage positive adoption changes among residents and HOA stakeholders. Findings in this article suggest many HOA dwellers are unsure whether they are permitted to engage in pollinator gardening, and they may perceive that this approach to landscaping is incompatible with neighborhood norms. These barriers must be addressed at the resident and HOA leadership levels  to help more people engage in gardening to support pollinators.